Presence of Clock genes in equine full-term placenta. (25th March 2020) - Parsons Aubone, Agata M; Bisiau, Christian M; McCue, Patrick M; Bouma, Gerrit J
Abstract: Mammals have a circadian rhythm that is synchronized by a master clock located in the hypothalamic suprachiasmatic nucleus (SCN ). The SCN regulates additional clocks located in peripheral tissues, including some involved in endocrine or reproductive functions. Studies in humans and mice report that molecular clocks also exist in the placenta. However, little is known about the presence of "Clock genes, " namely Circadian Locomotor Output Cycles Kaput ( CLOCK ), Brain and Muscle Arnt-Like 1 ( BMAL1 ), Period 1 ( PER1 ), Period 2 ( PER2 ), Cryptochrome 1 ( CRY1 ), and Cryptochrome 2 ( CRY2 ), in equine placenta. Pregnancy length in mares varies and shows fluctuations in hormone concentrations throughout pregnancy. We postulate that similar to humans and mice, Clock genes are present in the horse placentas. Our goal was to determine if relative levels of clock genes were different between placentas associated with males and female fetuses or correlated with gestational length. We used polymerase chain reaction and immunofluorescence to study the presence of CLOCK, BMAL1, PER1, PER2, CRY1, and CRY2 in full-term mare placentas. Clock genes were present in all placentas, with significant lower levels of CRY2 and CLOCK in placentas that were associated with male fetuses. There was no association between relative levels of Clock genes and gestational length. These data provide the stage for future studies aimed at uncovering a function for Clock genes in the horse placenta.